The Roles of circRNAs in Liver Cancer Immunity - Tang, Ying; Jiang, Mei; Jiang, Hai-Mei; Ye, Zeng Jie; Huang, Yu-Sheng; Li, Xiu-Shen; Qin, Bin-Yu; Zhou, Rui-Sheng; Pan, Hua-Feng; Zheng, Da-Yong (Frontiers in Oncology, 2021)
Liver cancer is one of the most common malignant tumors. Natural killer (NK) cells play an important role in the natural antitumor immune response. In recent years, NK cell dysfunction has been demonstrated in liver cancer. However, the molecular biological mechanism of NK cell dysfunction in liver cancer is still unclear. CircRNAs are stable covalently closed non-coding RNAs. Many studies indicate that circRNAs are involved in the pathological and physiological processes of liver cancer. In this review, we summarized the functions of circRNAs in liver cancer, including proliferative, metastasis and apoptosis, liver cancer stemness, cell cycle, immune evasion, glycolysis, angiogenesis, drug resistance/sensitizer, and senescence. Immune escape is considered to be one of the hallmarks of cancer development, and circRNAs predominantly affects NK cells in the immune microenvironment of liver cancer. CircRNAs may be a potential marker for liver cancer and provide new ideas for the study of NK cells in liver cancer.